Demographic characteristics with compliance on the implementation of health protocol on passenger ship - Asmoro, Candra Panji; Prasetya, Robby Bagus; Retno, (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the relationship of demographic characteristics with coronavirus disease-2019 protocol compliance among ship passengers. Method: The descriptive, correlational, cross-sectional study was conducted in May 2022 at the harbour in East Java, Indonesia, after approval from the ethics review committee of Universitas Airlangga, Indonesia, and comprised individuals of either gender aged 18-65 years who had a passenger ship departure ticket and were able to communicate well in the Indonesian language. Data related to demographic characteristics and coronavirus disease-2019 standard protocol compliance. Data was analysed using SPSS 25. Results: Of the 157 subjects, 71(45.2%) were males, 86(54.8%) were females, 68(43.3%) were aged 26-45 years, 79(50.2%) had studied up to the bachelor’s level,106(66.2%) were employees, 89(56.7%) had earnings below the provincial standard, and 116(73.9%) were married. Health protocol compliance at the harbour had a significant correlation with gender, age, education, occupation and income (p<0.05). Conclusion: The factors related to the compliance of the coronavirus disease-2019 protocol at the harbour were gender, age, education, occupation and income. Keywords: COVID-19, Mask, Marital, Ethnicity, Occupations.